Green Synthesis and Morphological Evolution for Bi2Te3 Nanosystems via a PVP-Assisted Hydrothermal Method - Fang Zhou; Weichang Zhou; Yujing Zhao; Li Liu (Nanomaterials, 2023)
Bi<semantics>2</semantics>Te<semantics>3</semantics> has been extensively used because of its excellent thermoelectric properties at room temperature. Here, 230–420 nm of Bi<semantics>2</semantics>Te<semantics>3</semantics> hexagonal nanosheets has been successfully synthesized via a “green” method by using ethylene glycol solution and applying polyvinyl pyrrolidone (PVP) as a surfactant. In addition, factors influencing morphological evolution are discussed in detail in this study. Among these parameters, the reaction temperature, molar mass of NaOH, different surfactants, and reaction duration are considered as the most essential. The results show that the existence of PVP is vital to the formation of a plate-like morphology. The reaction temperature and alkaline surroundings played essential roles in the formation of Bi<semantics>2</semantics>Te<semantics>3</semantics> single crystals. By spark plasma sintering, the Bi<semantics>2</semantics>Te<semantics>3</semantics> hexagonal nanosheets were hot pressed into solid-state samples. We also studied the transport properties of solid-state samples. The electrical conductivity <semantics>σ</semantics> was 18.5 × 10<semantics>3</semantics> Sm<semantics>−1</semantics> to 28.69 × 10<semantics>3</semantics> Sm<semantics>−1</semantics>, and the Seebeck coefficient S was −90.4 to −113.3 µVK<semantics>−1</semantics> over a temperature range of 300–550 K. In conclusion, the observation above could serve as a catalyst for future exploration into photocatalysis, solar cells, nonlinear optics, thermoelectric generators, and ultraviolet selective photodetectors of Bi<semantics>2</semantics>Te<semantics>3</semantics> nanosheet-based photodetectors.